The Human Immunodeficiency Virus in rural areas: reflections from the perspective of access to health services (Research, Society and Development, 2021)
Introduction: Rural areas are the object of evident social negligence that reflects in the context of public health, as a result of the characterization, specificity and concentration of services in large urban centers. These factors corroborate the spread of diseases in these locations, such as HIV/AIDS, which has been undergoing a process of “internalization” over the years. Objective: This study aimed to analyze, in the literature, the management of actions to counter the Human Immunodeficiency Virus (HIV) in rural areas, emphasizing the access of individuals in these locations. Methodology: An Integrative Literature Review was carried out in the PubMed and BVS databases, with the research resulting in 18 articles that met the inclusion and exclusion criteria. Results: The studies highlighted the apartment of services as a barrier to access, moreover the focus of actions for women. The social stigma was a relevant factor for users' non-adherence to services. Conclusion: The rural population still lives with deficits in access to health services, so it is necessary to create strategies that consider the specificities of individuals who live in this context, mainly with a focus on combating HIV/AIDS.